O Marquês de Pombal e os ingleses: a contribuição de Thomas Mun para instrução pública (1571-1641) - Santos, José Augusto Batista dos (2023)
Relations between Portugal and England are marked by moments of distancing and approximations. In fact, there are mixed feelings with regards to the role played by England in decisive events in the history of Portugal. Such feelings, at times, took the shape of aversion towards everything considered English and, on other occasions, they gave rise to some sort of admiration for the achievements of the English as a people. That made it possible for the formation of multiple representations about the latter. Therefore, this research investigates the way in which Pombal’s representations about England – and the English – contributed to the reforms in education. From a general perspective, it deals with the impact that the contacts with the English nation made on Pombal’s writings and eventually on his political action. From a particular perspective, it concentrates on Thomas Mun, an English Merchant considered by many to be one of the representatives of what came to be known as mercantilism. Our thesis is that some of this merchant’s ideas were used by Sebastião José to implement his reforms in education, especially for the creation of the School of Commerce. Therefore, we revisited the relations between the two nations, highlighting, whenever necessary, the oscillations which characterized them. It was also necessary to contrast the manner by which such relations were represented in various texts written in different moments in the history of Portugal, using as a milestone the centenaries of Pombal’s death. It has become evident that the ideias heralded by Thomas Mun in the 17th century, and advocated by Malachy Postlethwayt – one of his followers and contemporary to Pombal – were appropriated by the marquis to reform public instruction. Such appropriations come to light in the Relação dos Gravames as well as in the Estatutos da Aula de Comércio.